Snow damage in plantations of Austrian pine and Scots pine in the western part of the Republic of Srpska - Zoran Stanivuković; Ranko Vasiljević (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci)
The paper presents research related to the harmful effects of snowfall in Austrian pine and Scots pine plantations in the western part of the Republic of Srpska. The most common types of tree damage are snow break and snowfall. The harmful effect of snow is more present in Scots pine plantations and at lower altitudes. Also, the harmful effect of snow is reflected in the reduction of the vitality of damaged trees, which become suitable for the attack of other harmful biotic factors, primarily harmful insects and fungi.